Holter monitoring in acute cerebrovascular patients without primary heart disease - Alioglu, Zekeriya; Bostan, Mehmet; Alioglu, Yurdan; Ozmenoglu, Mehmet; Bayram, Ali (Annals of Medical Research, 2021)
None
Keywords: s : Acute cerebrovascular disease, holter monitoring